Antibiotic use in ambulatory care for acutely ill children in high-income countries: a systematic review and meta-analysis. Issue 12 (10th August 2022) - Burvenich, Ruben; Dillen, Hannelore; Trinh, Nhung T H; Freer, Joseph; Wynants, Laure; Heytens, Stefan; De Sutter, An; Verbakel, Jan Y
Abstract : Objective: To determine the rate and appropriateness of antibiotic prescribing for acutely ill children in ambulatory care in high-income countries. Design: On 10 February 2021, we systematically searched articles published since 2000 in MEDLINE, Embase, CENTRAL, Web Of Science and grey literature databases. We included cross-sectional and longitudinal studies, time-series analyses, randomised controlled trials and non-randomised studies of interventions with acutely ill children up to and including 12 years of age in ambulatory care settings in high-income countries. Pooled antibiotic prescribing and appropriateness rates were calculated using random-effects models. Meta-regression was performed to describe the relationship between the antibiotic prescribing rate and study-level covariates. Results: We included 86 studies comprising 11 114 863 children. We found a pooled antibiotic prescribing rate of 45.4% (95% CI 38.2% to 52.8%) for all acutely ill children, and 85.6% (95% CI 73.3% to 92.9%) for acute otitis media, 37.4% (95% CI 30.9% to 44.3%) for respiratory tract infections, and 40.4% (95% CI 29.9% to 51.9%) for other diagnoses. Considerable heterogeneity can only partly be explained by differences in diagnoses. The overall pooled appropriateness rate is 68.5% (95% CI 55.8% to 78.9%, I²=99.8%; 19 studies, 119 995 participants). 38.3% of all prescribed antibiotics were aminopenicillins. Conclusions: Antibiotic prescribing rates for acutely ill children in ambulatory care in high-income countries remain high. Large differences in prescription rates between studies can only partly be explained by differences in diagnoses. Better registration and further research are needed to investigate patient-level data on diagnosis and appropriateness. Abstract : This systematic review analyzed studies including over 11 million children to determine the rate and appropriateness of antibiotic prescribing for acutely ill children in outpatient settings. They found high prescribing rates, and differences only partially explained by diagnosis.